Laha Bete as a Traditional Culinary Typical of Sinjai Regency - Ati Rukmana (Media Pendidikan Gizi dan Kuliner, 2021)
Each community has a unique culinary that reflects their respective regions. In Sinjai Regency, there is Laha Bete which is processed from anchovy which is a marine product of the Sinjai community. This paper intends to describe the traditional food of Laha Bete as a legacy from the ancestors to be known together. The method used in collecting research data is a qualitative research method, which includes in-depth interviews with informants and observations of the object of study and the collection of related documents. The processing of Laha Bete is unique because it is processed through vinegar immersion which has long been known by the public. The materials used in the past and present have been added as a result of the development of the times and the knowledge possessed by the community. The ingredients used in the past were only anchovies, grated coconut and salt for flavoring. But now there are additional ingredients such as vetsin, fried shallots, sliced red chilies, basil leaves or soup leaves. In the past, coastal communities only made Laha Bete as family consumption, but its development is now presented in activities or celebration parties held by the people of Sinjai Regency.